THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND FAMILY SUPPORT WITH STUDENT ACHIEVEMENT IN HISTORY AT SMA NEGERI 1 PANCUR BATU - Khoiriyah Nurul Abdulloh; Suaidah Lubis; Lahmuddin Lubis (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the relationship between emotional intelligence and family support with achievement in history lessons at SMA Negeri 1 Pancur Batu. Student achievement is related to how students get the quality or effectiveness of the level of learning achievement consisting of objectives, learning materials, strategies, learning tools, students and teachers. The hypothesis put forward is that there is a positive relationship between emotional intelligence and family support with student achievement in high school students. The sampling technique used purposive sampling, a sample of 117 students. This research uses emotional intelligence scale and family support scale. The method of data analysis is analysismultiple regression.Based on the data analysis carried out, the research results are obtained: 1) there is a significant positive relationship between Emotional Intelligence and History Lesson Achievement seen from the value of the determinant coefficient (Rxy) = 0.425 with p = 0.000 <0.050; 2) there is a significant positive relationship between family support and history achievement in terms of the value of the determinant coefficient (Rxy) = 0.655 with p = 0.000 <0.050; and 3) there is a significant positive relationship between Emotional Intelligence and Family Support with History Achievement as seen from the value of the determinant coefficient (Rxy) = 0.557 with p = 0.000 <0.050.